STUDY WEAR TOOL WITH HIGH-SPEED MILLING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
This report examined tool wear in high-speed machining of tool steel with a hardness of HRC 63. Wear monitored periodically using the device for automatic geometric correction tool (length and radius) situated in the working area of the machine. The study was conducted on milling machine RAIS M400 with CNC Heidenhain iTNC 530i.